(untitled) (American Journal of Technology and Applied Sciences, 2025)
Improving livestock productivity largely depends on the development of a robust forage base. This forage base is strengthened through the cultivation of high-nutrition crops on agricultural lands. Among these, corn stands out as one of the most important forage crops in animal husbandry due to its high yield potential. Its cultivation significantly increases the amount of feed units harvested per hectare. Moreover, corn grain is widely used in the production of high-quality compound feeds. One of the key factors in maximizing grain yield is determining the optimal plant density. This article presents the findings of research aimed at identifying the most suitable seedling density for achieving high grain productivity in the newly developed corn variety "Uzbekistan-2018."